A Novel Concept of Hybrid Treatment for High‐Hardenability Steels: Concomitant Hardening and Paraequilibrium Thermochemical Treatment to Produce Interstitially Hardened/Stabilized Austenite Surfaces. Issue 10 (31st August 2020) - Toscano, Tarciana D.; Cardoso, Rodrigo P.; Brunatto, Silvio F.
Abstract : A novel concept of hybrid treatment for steels is presented. The goal is to produce a hard interstitially hardened/stabilized austenite layer, with an expected improved wear and corrosion resistance, in the surface of high‐hardenability steels. The novelty is in the fact that the thermochemical treatment is performed in the steel metastable austenite field, above the martensite start temperature, during the isothermal step of the martempering or austempering hardening treatment. As a proof of concept, CA6NM martensitic stainless steel samples are subjected to the novel hybrid treatment. The whole treatment is plasma assisted and the chosen thermochemical treatment is nitriding. In the presented case, the produced hard layer is constituted of N‐stabilized austenite. During the paraequilibrium thermochemical treatment step, the metastable austenite surface is converted into a hard interstitially hardened/N‐stabilized austenite. Once concluded the whole treatment, as the component is cooled down to the room temperature, surface does not undergo phase transformation, whereas the nonchemically altered substrate bulk undergoes metastable austenite to martensite phase transformation. So, by means of this case study, the feasibility and potentiality of this novel concept of hybrid treatment is proved. Abstract : Herein, an innovative hybrid treatment, suitable for high‐hardenability steels, is proposed and a case study is presented to prove the concept. The treatment enables to obtain a layer of a hard interstitially hardened/stabilized austenite over a martensitic component. The treated layer is expected to present higher wear and corrosion resistance than the martensitic substrate bulk.